Kekerabatan merpati hias (Columba livia) dilihat dari profil protein darah - Harmoko Harmoko; Ummie Lestari (Universitas Sebelas Maret, 2022)
Objective: The purpose of this study was to predict the kinship of ornamental pigeons based on blood proteins.Methods: The research method used is exploratory descriptive with a laboratory observation-based approach. Research procedures include: Blood Sampling, Blood Protein Isolation, Purification, Measurement of concentration with a nanodrop spectrophotometer and Electrophoresis. Data analysis includes: Protein Band Profile and Determination of Protein Molecular Weight with RF formula and Relationship with MVSP version 3.22 program.Results: The protein profile in the plasma of ornamental pigeons is different from one type of pigeon to another. some of the protein appears in the ornamental pigeon species but does not appear in other breeds. Likewise with the target protein to be analyzed, some are expressed and some are not expressed in ornamental pigeons. Results based on the analysis of protein profiles and dendograms of the four specific proteins (hemoglobin, transferrin, posttransferrin, and immunoglobulin) contained in erythrocytes and blood plasma, it can be seen that there are two clusters. Cluster 1 is occupied by varieties of ornamental pigeons Moven and cluster 2 is occupied by varieties of ornamental pigeons Lahore, American fantail, Vienna, Indian Fantail, King, Capucine, Gondok and Modena.Conclusions: The results of the ornamental pigeon kinship prediction based on blood protein showed that each variety had different kinship relationships. King, Capucine, Gondok and Modena pigeons have the closest relationship, and Moven pigeons have the most distant relationship from the researched ornamental pigeons.